2010
DOI: 10.1179/147683010x12611460764363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anserine ingestion on hyperglycemia and the autonomic nerves in rats and humans

Abstract: Anserine and L-carnosine are similar dipeptides synthesized by muscles of vertebrates. The functional role of anserine is unknown, although previous studies showed hypoglycemic effects of carnosine through autonomic nerves. Thus, we evaluated the effects of anserine on blood glucose levels and the neural activities. Intraperitoneal administration of specific doses of anserine to hyperglycemic rats reduced hyperglycemia and plasma glucagon concentrations, whereas thioperamide eliminated the effects of anserine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In more detail, carnosine lowers neuronal activities of sympathetic nerves and facilitates those of parasympathetic nerves causing both an increase in the insulin secretion and suppression in the glucagon secretion from the pancreas, resulting in a hypoglycemic effect. A similar hypoglycemic effect was more recently reported for anserine, which was also found to reduce blood glucose levels in humans during oral glucose tolerance testing (224). A direct correlation of carnosine serum levels with insulin levels was also detected by Sauerhoefer et al (326) in db/db and hCN1 transgenic db/db mice, whereas peripheral insulin sensitivity was unaltered.…”
Section: B Diabetessupporting
confidence: 78%
See 1 more Smart Citation
“…In more detail, carnosine lowers neuronal activities of sympathetic nerves and facilitates those of parasympathetic nerves causing both an increase in the insulin secretion and suppression in the glucagon secretion from the pancreas, resulting in a hypoglycemic effect. A similar hypoglycemic effect was more recently reported for anserine, which was also found to reduce blood glucose levels in humans during oral glucose tolerance testing (224). A direct correlation of carnosine serum levels with insulin levels was also detected by Sauerhoefer et al (326) in db/db and hCN1 transgenic db/db mice, whereas peripheral insulin sensitivity was unaltered.…”
Section: B Diabetessupporting
confidence: 78%
“…The metabolic instability of carnosine in human serum due to the presence of carnosinase has prompted a great interest in the design and chemical synthesis of novel carnosine derivatives, as well as in research towards the therapeutic potential of the natural carnosine derivatives, such as anserine (224). These compounds are more resistant to carnosinase, while maintaining or even improving some beneficial effects of the parent compound, such as the antioxidant and metal ion chelating ability or the reactivity with RCS.…”
Section: A Extrapolation Of Animal Models Of Disease To Humansmentioning
confidence: 99%
“…The finding would suggest either an increase in sympathetic nervous system activity or a decrease in vagal activity after drinking EOC. This is in contrast to animal research which suggested that carnosine/anserine reduced sympathetic and increased parasympathetic nervous system activity [9,10]. However, this research was conducted using anaesthetised rats and it is possible that different results would have occurred when awake.…”
Section: Discussionmentioning
confidence: 78%
“…Carnosine has been found to inhibit neural activities of sympathetic efferent nerves innervating the adrenal gland and liver, and in rats, facilitates the activity of the vagal celiac nerve that innervates the pancreas [9]. Similarly, after laparotomy an intraduodenal injection of anserine to anaesthetized rats suppressed sympathetic nerve activity and enhanced the activity of the vagal gastric efferent [10]. These mechanisms are thought to mediate the anti-hyperglycaemic effects of carnosine and anserine [11]; however, to our knowledge these effects have not been studied in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, this notion has not provided any explanation for the synthesis of anserine which shows buffer capacity similar to that of carnosine. Recently, histidine-containing dipeptides have been considered to exert a more complex effect on cell and tissue metabolism via their potent antiglycemic [5], [6], antiglycation [7] and antioxidant properties [8]. Unfortunately, no definitive explanation of their physiological importance has been provided.…”
Section: Introductionmentioning
confidence: 99%